Family Design in Advertisements: The Case of Türkiye and Uzbekistan - Gulina Yusupova (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
In the digital age, mass media is used to shape new perceptions, thereby altering individuals’ thought processes and social norms. Media content is also an effective tool for reshaping values and beliefs. Television, which families use for socializing, is not only part of daily life, but also an effective means of transmitting cultural values. Advertisements, a significant source of income for television channels, also influence the formation and reconstruction of family structures. This study examines how family structures are represented in television advertisements, focusing on family life, the relationships between family members, and the design of social roles within the family. It also considers whether the families depicted in the advertisements correspond to real-life family structures. The study sample was selected from family-themed advertisements shown during the Teşkilat series on TRT1 in Turkey and the Hojar series on the Yoshlar state channel in Uzbekistan, including the ‘Cola Turka’ and ‘Halkbank’ advertisements, and the ‘Uzum Market’ and ‘Beeline’ advertisements. The study data were analyzed using Gerbner’s bread theory and content analysis, a qualitative research method. After presenting the content of each advertisement, the effects of the advertisements on family members and viewers are discussed alongside the analysis. According to the research results, advertisements in Turkey depict nuclear and modern families, whereas those in Uzbekistan depict traditional and extended families. The study concluded that the family types presented in the advertisements correspond to actual family structures in Turkey and Uzbekistan and also reinforce existing family structures. The findings revealed that, despite being Turkic peoples, the families in Turkey and Uzbekistan exhibit distinct differences.